The Role of Entrepreneurial Agility in Enhancing the Entrepreneurial Intentions of Generation Z Womenpreneurs: A Systematic Literature Review - Ericha Tiara Hutamy; Muhammad Hasan; Inanna (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the role of entrepreneurial agility (EA) in enhancing the entrepreneurial intentions of Generation Z womenpreneurs through theoretical perspectives and recent empirical evidence. In the rapidly evolving digital economy, entrepreneurs are required to adapt to market changes, manage uncertainty, and effectively capitalize on emerging opportunities. EA serves as a key capability that drives these abilities, especially for a generation that has grown up closely with technology. This study employs a Systematic Literature Review (SLR) method using the PRISMA 2020 protocol, with literature searches conducted through the Scopus and Google Scholar databases over the past five years, yielding a total of 244 articles (Scopus = 44 articles from 2020–2025 and Google Scholar = 200 articles from 2020–2025). The SLR findings indicate that Generation Z women possess substantial potential to develop digital-based businesses, yet they still face obstacles such as limited experience, fear of failure, and gender disparities. In this context, EA emerges as a determining factor that can enhance confidence, risk-taking readiness, and resilience in navigating business dynamics. Thus, strengthening EA is not only theoretically relevant but also practically essential to support the development of young womenpreneurs in the digital economy era.